Sustainability Analysis of Carocok Painan Beach Area Management in Pesisir Selatan Regency - Ricki Gushendrio; Umar Mansyur; M. Mujio (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
The Carocok Beach tourist area has tourism potential that can be developed because it is located on the coast and is easily accessible and close to the center of Painan city. This tourist area needs to consider its sustainability so that the next generation can enjoy it. The aim of this research is to analyze the sustainability status of the Carocok Painan Beach Area. The research method is qualitative and quantitative with the Multidimensional Scaling (MDS) analysis technique with the Rapid Appraisal Index Rap-fish modified into Rap-ecotourism. The sustainability status of the Carocok Painan Beach tourist area is included in the quite sustainable category with an average index value of 57.37. The index values for the 5 dimensions are the ecological dimension quite sustainable (56.16), the economic dimension quite sustainable (51.29), the social dimension quite sustainable (54.63), the infrastructure dimension quite sustainable (63.01), and the laws and institutions are quite sustainable (61.76).